Analysis of Omni Channel Strategy in Digital Retail on Modern Indonesian Consumer Behavior: Analisis Strategi Omni Channel dalam Ritel Digital terhadap Perilaku Konsumen Indonesia Modern - Baso, Farisha Andi; Sitorus, Santa Lusianna; Meilinda, Vivi; Anjani, Sheila Aulia; Rodriguez, Marta (ADI Publisher, 2025)
The development of digital technology has driven a profound transformation in the retail industry, giving rise to the omni-channel strategy as a holistic ap proach to meet modern consumer expectations. This study aims to analyze the influence of online and offline channel integration on Indonesian consumer behavior in the context of digital retail. Using a qualitative approach through literature review and secondary data analysis, this study reveals that today’s In donesian consumers show a high preference for convenience, personalization, and speed of service in the shopping experience. An omni-channel strategy enables companies to provide a consistent, adaptive, and integrated consumer journey across various interaction points, which has a positive impact on customer loyalty and operational efficiency. Furthermore, the implementation of this strategy aligns with sustainability principles, particularly in supporting Sustainable Development Goals (SDGs) 9 (industrial and infrastructure innova tion) and point 12 (responsible consumption and production). These findings confirm that the success of digital retail in Indonesia is highly dependent on the ability of business actors to strategically manage channel integration, under stand evolving consumer behavior, and prioritize sustainability values in their operations.